Abetalipoproteinemia: a case report - Özsoylu, Şinasi; Koçak, Nurten; Gürakar, Figen; Renda, Nurten (The Turkish Journal of Pediatrics, 1985)
A six-month-old girl, with abetalipoproteinemia is presented here, the first report of this syndrome from Turkey. She was the child of first cousins, and was referred to Hacettepe Children’s Hospital with hemolytic anemia with severe acanthocytosis, severe malnutrition and hepatomegaly. Diagnosis was made by lipid electrophoresis studies in the patient and in both parents. Only high density lipoproteins were seen in the patient’s electrophoresis results, but with both parents the findings were normal.